Examination of the Relationships between Secondary School Students’ Social Media Attitudes, School Climate Perceptions and Levels of Alienation - Deniz, Emrullah; Kazu, Hilal (Athens Institute for Education and Research, 2022)
The aim of this research is to examine the relationships between social media attitudes, school climate perceptions and level of alienation of students studying in secondary schools. In the 2018-2019 academic year, 418 students from various secondary schools in Mardin participated in the study. Descriptive statistics and structural equality model were used in the analysis of the data. As a result of the research, it was determined that the level of alienation variable is positively affected by sharing needs, social isolation and safe learning environment; the safe learning environment variable is negatively affected by the social competence variable while it is affected positively by the social isolation variable. Besides, the safe learning environment as a mediator resulted in negative effects between the need for sharing and alienation, positive ones between social isolation and alienation, negative ones between social competence and alienation, and finally negative effects between relationships with teachers and alienation. According to the results, it can be stated that creating a supportive school climate for students in educational settings will reduce students’ tendency to use social media networks and prevent them from becoming alienated by making more friend. © 2022, Athens Institute for Education and Research. All rights reserved.
Keywords: Alienation; School climate; Social media; Structural equality model